2017
DOI: 10.1103/physrevlett.118.061602
|View full text |Cite
|
Sign up to set email alerts
|

Graviton and Gluon Scattering from First Principles

Abstract: Graviton and gluon scattering are studied from minimal physical assumptions such as Poincare and gauge symmetry as well as unitarity. The assumptions lead to an interesting and surprisingly restrictive set of linear equations. This shows gluon and graviton scattering to be related in many field and string theories, explaining and extending several known results. By systematic analysis exceptional graviton scattering amplitudes are derived which in general dimensions can not be related to gluon amplitudes. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 30 publications
3
43
0
Order By: Relevance
“…The polarization dependence of the latter is like in YangMills case, e.g. no contractions of the form ( · k) n [2][3][4], but amplitudes produced by F 3 certainly contain such contractions. In this sense, F 3 is the first higher-dimensional operator with genuinely new polarization structures in the amplitudes.…”
Section: Introduction and Motivationsmentioning
confidence: 92%
“…The polarization dependence of the latter is like in YangMills case, e.g. no contractions of the form ( · k) n [2][3][4], but amplitudes produced by F 3 certainly contain such contractions. In this sense, F 3 is the first higher-dimensional operator with genuinely new polarization structures in the amplitudes.…”
Section: Introduction and Motivationsmentioning
confidence: 92%
“…We should perhaps note that Lagrangians with similar operators have previously been studied for phenomenological reasons in [13][14][15][16][17][18] and because the operators arise as corrections in the α expansion of bosonic open string theory [19][20][21]. It is however the specific theory introduced in [6] that interests us as it satisfies color-kinematics duality and gives conformal gravity through the double copy.…”
Section: (Df ) Theorymentioning
confidence: 99%
“…It was shown by Boels and Medina [7] that higher-point Einstein-Hilbert amplitudes can be obtained from the 3-point amplitude by imposing the symmetry and unitarity conditions. Furthermore this is the only amplitude (among the two possible ones that we found here) that corresponds to a constructible theory [5], and as predicted by the famous KLT relation between open and closed strings [24].…”
Section: Jhep12(2017)048mentioning
confidence: 99%
“…Benincasa and Cachazo used BCFW to investigate a class of "constructible" theories and found that there are no nontrivial amplitudes of different species of spin-2 particles or particles with spin larger than 2 among this class of theories, while a theory with a single kind of spin-2 particles is unique. Lately Boels and Medina [7] have obtained the threepoint amplitudes using the constraints of on-shell gauge invariance. Their results are expressed in terms of polarization tensors with the gauge transformations manifest; these have been done for polarization vectors and rank-2 polarization tensors, but not for general polarizations.…”
Section: Jhep12(2017)048mentioning
confidence: 99%